Role of DNA minor groove interactions in substrate recognition by the M.SinI and M.EcoRII DNA (cytosine-5) methyltransferases - Kiss, Antal (Oxford University Press, 2001)
The SinI and EcoRII DNA methyltransferases recognize sequences (GG(A)/(T)CC and CC(A)/(T)GG, respectively), which are characterized by an (A)/(T) ambiguity. Recognition of the A·T and T·A base pair was studied by in vitro methyltransferase assays using oligonucleotide substrates containing a hypoxanthine·C base pair in the central position of the recognition sequence. Both enzymes methylated the substituted oligonucleotide with an efficiency that was comparable to methylation of the canonical substrate. These observations indicate that M.SinI and M.EcoRII discriminate between their canonical recognition site and the site containing a G·C or a C·G base pair in the center of the recognition sequence (GG(G)/(C)CC and CC(G)/(C)GG, respectively) by interaction(s) in the DNA minor groove. M.SinI mutants displaying a decreased capacity to discriminate between the GG(A)/(T)CC and GG(G)/(C)CC sequences were isolated by random mutagenesis and selection for the relaxed specificity phenotype. These mutations led to amino acid substitutions outside the variable region, previously thought to be the sole determinant of sequence specificity. These observations indicate that (A)/(T) versus (G)/(C) discrimination is mediated by interactions between the large domain of the methyltransferase and the minor groove surface of the DNA.